Multi-Omic Investigation of Low-Nitrogen Conditional Resistance to Clubroot Reveals Brassica napus Genes Involved in Nitrate Assimilation - Aigu, Yoann; Daval, Stéphanie; Gazengel, Kévin; Marnet, Nathalie; Lariagon, Christine; Laperche, Anne; Legeai, Fabrice; Manzanares-Dauleux, Maria J.; Gravot, Antoine (Frontiers in Plant Science, 2022)
Nitrogen fertilization has been reported to influence the development of clubroot, a root disease of Brassicaceae species, caused by the obligate protist Plasmodiophora brassicae. Our previous works highlighted that low nitrogen fertilization induced a strong reduction of clubroot symptoms in some oilseed rape genotypes. To further understand the underlying mechanisms, the response to P. brassicae infection was investigated in two genotypes ’Yudal’ and HD018 harboring sharply contrasted nitrogen-driven modulation of resistance toward P. brassicae. Targeted hormone and metabolic profiling, as well as RNAseq analysis, were performed in inoculated and non-inoculated roots at 14- and 27-days post inoculation, under high and low-nitrogen conditions. Clubroot infection triggered a large increase of SA concentration and an induction of the SA gene markers expression whatever the genotype and nitrogen conditions. Overall, metabolic profiles suggested that N-driven induction of resistance was independent of SA-signaling, soluble carbohydrate and amino-acid concentrations. Low-nitrogen driven resistance in ‘Yudal’ was associated to the transcriptional regulation of a small set of genes, among which the induction of NRT2- and NR-encoding genes. Altogether, our results indicate a possible role of nitrate transporters and auxin signaling in the crosstalk between plant nutrition and partial resistance to pathogens.